Toxic agents conjugated to proteins recognizing surface receptors in the treatment of acute myeloid leukemia - Paluszewska, Monika (Contemporary Oncology/Współczesna Onkologia, 2001)
Classical therapy of acute myeloid leukemia remains unsatisfactory. Recent advances in understanding the biology of acute myeloid leukemia have lead to the development of targeted treatment strategies. This review presents the biological properties and therapeutic uses of drugs targeted to surface antigens (monoclonal antibodies, immunotoxins, radioimmunoconjugates and cytokine-toxin fusion proteins). Although the preliminary results with these targeted therapies are promising, further studies are needed to establish their role in the treatment of acute myeloid leukemia.